THE ROLE OF ISLAMIC RELIGIOUS EDUCATION TEACHERS IN INCREASING STUDENTS' RELIGIOUS AWARENESS - Ifham Choli; Muhammad Fikri Rachman (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2023)
Religious awareness is an attitude, experience, feeling and religious behavior that occurs within a person which is organized in the mental system of the personality of each individual. Religion involves all the functions of the human body and soul, so religious awareness also includes affective, conative, cognitive and motor aspects. The involvement of the affective and conative aspects appears in the experience of God, religious feelings and longing for God. The cognitive aspect is seen in the attitude of faith and belief, while the involvement of motor functions can be seen from the actions and movements of religious behavior. The research methodology used in this study is a qualitative research method with observation-based data collection techniques. The aim of this study was to determine the teacher's role in building religious awareness in students. The results of his research are that teachers familiarize students with religious practices and habits, create affection and harmonious relationships between teachers and students, motivate students to memorize selected verses of the Al-Qur'an, provide understanding and awareness to students of the importance of Islamic Religious Education , accustom students to always apply commendable traits and good morals.